Force Entrepreneurship in Contemporary Russia. Part 7 - Вадим Викторович Волков (Journal of Economic Sociology, 2010)
The chapter deals with an important aspect of Soviet state heritage, that was not studied carefully before. The puzzle of the lack of state impact could be partially solved by the research of “quite” changes of large segments of state forced organizations into the system of private guarding services.  The powerful tool of the compulsion of the former Soviet Union that became useless due to these changes could not disappear without a trace. It only changed by the organizational shape: private companies appeared and started to provide guard services and information support. The employees of these companies are the former staff of state security and militia.  The author analyses these important newcomers on the market, their background, fields of business and their relations with other force structures as well as their future development.